PENGARUH MEDIA EDUKASI KARTU KUARTET TERHADAP PENGETAHUAN, EFIKASI DIRI, DISPAREUNIA PEREMPUAN MENOPAUSE - Iryanti, Iryanti; Hilman, Asep Fithri; Karjatin, Atin (Media Penelitian dan Pengembangan Kesehatan, 2024)
Health development has increased life expectancy, consequently, the population of menopausal women has increased. Menopause causes problems including dyspareunia. Limited information on dyspareunia makes women worried and afraid when entering menopause period. Education may help them understand changes in their bodies. The research aimed to analyze the effect of quartet card educational media on knowledge, self-efficacy, dyspareunia of menopausal women. This research used pre-test and post-test method with control design. The sampling technique was purposive sampling and the sample was menopausal women experiencing dyspareunia determined through NRS, not having health-related educational background, literate, not senile. The exclusion criteria were menopausal women using anti-depressants, antihistamines, sedatives, progestin or estrogen birth control pills, having hormone therapy, history of sexual abuse, injury or infection in the genital area or urinary tract, and those who met both criteria were 70 people (35 people in each group). The independent variable was quartet card educational media on menopausal dyspareunia, and the dependent variables were knowledge, self-efficacy, dyspareunia. Knowledge was measured using instruments, self-efficacy was measured using GSE, and dyspareunia scale was measured using NRS questionnaire. Quartet card game was conducted twice, two weeks apart, approximately one hour for each session. Data were analyzed using Wilcoxon and Mann-Withney test. The test results revealed that quartet card educational media on menopausal dyspareunia increases knowledge and self-efficacy and reduces menopausal dyspareunia significantly, all with p-value= 0.000 < 0.05. The use of menopausal dyspareunia quartet card can overcome dyspareunia and reduce the prevalence of stress in menopausal women.